Subchronic oral toxicity study of Vegeta in Sprague-Dawley rats (Faculty of Medicine Universitas Indonesia, 2006)
The objective of this study was to determine the safety and toxic effect of Vegeta giving orally for a period of 90 days in rats. Eighty rats of Sprague-Dawley strain were randomly devided into 4 groups. Each group consists of 20 rats, 10 male and 10 female rats. Each group received 0.25 g/ kgBW; 0.50 g / kgBW; 1.00 g / kgBW Vegeta (in aquadest solution) respectively, and the control group received 5 mL /kgBW aquadest , given orally by gastric tube for 90 days. The ratâs body weight and behavior were daily evaluated. On the 90th day, the rats were decapitated and the blood samples were withdrawn for evaluation of Hemoglobin, leucocyte, SGPT, SGOT, creatinine, and ureum concentration. Visceral organs were also removed, being weighted and were examined microscopically. The results showed that Vegeta with dose of 0.25 g / kgBW; 0.50 g / kgBW, and 1.00 g / kgBW did not affect body weight, liver and renal function compared to control group. There was no significant difference for hemoglobin value compared to control group, but the number of leucocyte increased in 1.00 g / kgBW Vegeta dose group, which was possibly caused by infection. In Vegeta group, there was different spleen and brain weight in male rats, and different lung and heart weight in female rats compared to the control group. However, since it was not dose-related and there was no specific abnormality in microscopic examination compared to the control group, it was not indicated as Vegeta toxic effect. The No observed effect level (NOEL) value of Vegeta for 90 day oral administration in male and female rats of Sprague-Dawley strain was 1.00 g / kgBW. (Med J Indones 2006; 15:223-8)Keywords: Vegeta, subchronic toxicity, oral, rats